Value and Character Education in the Perspective of General Education in Higher Education - Fuadaturrahmah, Fuadaturrahmah; Ningtias, Sukma; Setiari, Doni; Tarigan, Ebenezer; Waruwu, Desnor Steven; Waruwu, Waruwu; Gulo, Delfin Masna; Putri, Dwi Agillia; Anggraini, Dhea Reni (Pusdikra-Publishing.com, 2024)
To effectively address the growing complexity of living conditions, its crucial to use a comprehensive and multidisciplinary approach. Engaging with experts from many scientific fields s crucial for finding tailored answers to complex problems that require knowledge from multiple disciplines. Library research s utilised to investigate and clarify data. This inquiry utilises literature the form of rules to assess the value and character education higher education from a general education perspective. The aim of this study s to examine and offer arguments concerning the subjects of value and character education higher education institutions Indonesia, focusing on the perspective of general education. Here s a brief overview of the findings from this investigation: General education, sometimes known as